A conceptual framework of immersive shared environments emphasizing social interaction - Kim, M.; Park, S.; Wang, Xiangyu (2015)
The effectiveness of visual displays has often been linked to the sense of presence embodied by immersive visualization. However, efforts analyzing how presence is associated with multi-users' quality of communication, including visualization capabilities to assist in architecture, engineering and construction (AEC), are still unfolding. This research is an exploratory study on social interaction, which aims to improve the presentation and communication of complex data through immersive simulation techniques. This paper reviews key concepts such as presence and immersion to identify factors that influence communication in the representative literature. It then introduces the Hub for Immersive Visualization and eResearch (HIVE) with a focus on the technological components. Finally it presents a conceptual framework of immersive shared environment, which enables multi-users to understand how to implement social interaction in a system efficiently or to determine whether a visualization system could support communication effectively. Future studies to validate the proposed framework are discussed, particularly in the context of cognitive factors in a shared environment.